2013
DOI: 10.1007/s10856-013-4892-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano-sized bioactive glass particles on the angiogenic properties of collagen based composites

Abstract: Angiogenesis is essential for tissue regeneration and repair. A growing body of evidence shows that the use of bioactive glasses (BG) in biomaterial-based tissue engineering (TE) strategies may improve angiogenesis and induce increased vascularization in TE constructs. This work investigated the effect of adding nano-sized BG particles (n-BG) on the angiogenic properties of bovine type I collagen/n-BG composites. Nano-sized (20-30 nm) BG particles of nominally 45S5 Bioglass® composition were used to prepare co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 52 publications
1
51
0
1
Order By: Relevance
“…Regarding bioactive glasses, particularly those of nominally Bioglass w 45S5 composition, the effects of their ionic dissolution products on the stimulation of endothelial cell proliferation, such as HUVECs, have been widely reported [13,20]. In addition, a recent work has confirmed the effects on the promotion of blood vessel growth by bioactive glass nanoparticles with the same composition as that previously mentioned, when they are incorporated in polymer-based scaffolds for BTE [81]. These considerations are in agreement with the results of our study, where the 2D scaffolds containing Nbg showed a higher proliferation of HUVECs and a better capability of forming tubes in Matrigel in comparison with those without Nbg.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding bioactive glasses, particularly those of nominally Bioglass w 45S5 composition, the effects of their ionic dissolution products on the stimulation of endothelial cell proliferation, such as HUVECs, have been widely reported [13,20]. In addition, a recent work has confirmed the effects on the promotion of blood vessel growth by bioactive glass nanoparticles with the same composition as that previously mentioned, when they are incorporated in polymer-based scaffolds for BTE [81]. These considerations are in agreement with the results of our study, where the 2D scaffolds containing Nbg showed a higher proliferation of HUVECs and a better capability of forming tubes in Matrigel in comparison with those without Nbg.…”
Section: Discussionmentioning
confidence: 82%
“…Such a composite matrix, when seeded with human-like osteoblast cells, has shown better osteoconductive properties compared to monolithic HA and has resulted in calcification of an identical bone matrix [160]. In another study, Vargas et al [161] investigated the effect of nano-sized Bioglass ® 45S5 (n-BG) particles, 20-30 nm in size, on the angiogenic properties of bovine type I collagen/n-BG composites. Two concentrations of n-BG were considered in this study (i.e., 10 wt% and 20 wt%).…”
Section: Bioceramic/polymer Composites For Bone Reconstructionmentioning
confidence: 99%
“…Two concentrations of n-BG were considered in this study (i.e., 10 wt% and 20 wt%). The addition of a limited concentration (10 wt%) of n-BG to collagen films induced an early angiogenic response, suggesting that this collagen/n-BG composition could be an attractive matrix for tissue engineering applications [161].…”
Section: Bioceramic/polymer Composites For Bone Reconstructionmentioning
confidence: 99%
“…Interestingly, so far only few investigations have been focused on the effects of the organic-BG interactions on the visco-elastic properties and structural recovery of composites. The influence of the BG particle size on the dynamic rheological changes over time (viscosity, storage and loss moduli) was recently investigated [6][7][8]. The main efforts aimed at tailoring the compositions and the textural properties of BG-organic carriers in order to improve the biomineralisation kinetics, i.e., the deposition of a surface apatite layer [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%